Development of locally homogeneous finite element model for simulating the mesoscale structure of asphalt mixture. (May 2021) - Du, Cong; Liu, Pengfei; Liu, Quan; Leischner, Sabine; Sun, Yiren; Chen, Jingyun; Oeser, Markus
Highlights: A novel locally homogeneous finite element method of asphalt mixture is proposed. The effectiveness and efficiency of this method are investigated and proven. A macroscale asphalt pavement model coupled with this method is simulated. Abstract: A locally homogeneous finite element (FE) model is proposed to account for the heterogeneous internal structures of asphalt mixtures in this study. For this model, the internal structure of the asphalt mixture was divided into several homogeneous parts based on digital image processing (DIP) technology. Within each part, one aggregate or air void inclusion was embedded in asphalt mortar, and the integral material properties were homogenized. By comparison with the currently used mesoscale heterogeneous FE models, the proposed locally homogeneous model was proven to be able to effectively consider the local enhancement of the aggregates especially at low frequencies and also consume much less computational time. In addition, the locally homogeneous asphalt mixtures were coupled into the macroscale asphalt pavement model to analyze the load-bearing capacity of the pavements. Comparing with a fully homogeneous pavement model, the computational results showed that the proposed locally homogeneous model can effectively represent the loading-bearing responses of asphalt pavements. This study indicates that this proposed FE simulation approach is able to balance the computational time and simulation effectivity and thus form a base for providing an efficient and robust platform for future development in the multiscale simulation of asphalt pavements.